Evaluación de un sistema de conductividad térmica en aislantes (2018)
This thesis project carried out in conjunction with the National Institute of Metrology focuses on the development of a national standard for the implementation of a system for measuring thermal conductivity in insulators. To establish this pattern, a primary method was selected, which is governed by ASTM C177 with a hot plate device that determines the thermal conductivity by measuring the normal heat flow in isothermal plates. Regarding the method, aspects such as the design criteria of the apparatus, the material of the samples, the distribution of the temperature in the hot plate and the guard, and the heat transfer in the annular space were taken into account.